Sources of endocrine‐disrupting compounds in North Carolina waterways: A geographic information systems approach. (15th January 2015) - Sackett, Dana K.; Pow, Crystal Lee; Rubino, Matthew J.; Aday, D. Derek; Cope, W. Gregory; Kullman, Seth; Rice, James A.; Kwak, Thomas J.; Law, Mac
Abstract The presence of endocrine‐disrupting compounds (EDCs), particularly estrogenic compounds, in the environment has drawn public attention across the globe, yet a clear understanding of the extent and distribution of estrogenic EDCs in surface waters and their relationship to potential sources is lacking. The objective of the present study was to identify and examine the potential input of estrogenic EDC sources in North Carolina water bodies using a geographic information system (GIS) mapping and analysis approach. Existing data from state and federal agencies were used to create point and nonpoint source maps depicting the cumulative contribution of potential sources of estrogenic EDCs to North Carolina surface waters. Water was collected from 33 sites (12 associated with potential point sources, 12 associated with potential nonpoint sources, and 9 reference), to validate the predictive results of the GIS analysis. Estrogenicity (measured as 17β‐estradiol equivalence) ranged from 0.06 ng/L to 56.9 ng/L. However, the majority of sites (88%) had water 17β‐estradiol concentrations below 1 ng/L. Sites associated with point and nonpoint sources had significantly higher 17β‐estradiol levels than reference sites. The results suggested that water 17β‐estradiol was reflective of GIS predictions, confirming the relevance of landscape‐level influences on water quality and validating the GIS approach to characterize such relationships. Environ Toxicol Chem 2014;9999:1–9. © 2014 SETAC